Impact of heat and nutritional stress on adaptive capability of bucks - Shilja Shaji (Academy of Climate Change Education and Research, 2015)
A study was conducted to assess the combined effect of heat stress and nutritional restriction on growth and reproductive performances in Osmanabadi Bucks. Twenty four adult Osmanabadi bucks (average body weight (BW) 16.0 kg) were used in the present study. The bucks were divided into four groups viz., C (n=6; control), HS (n=6; heat stress), NS (n=6; nutritional stress) and CS (n=6; combined stress). The study was conducted for a period of 45 days. C and HS bucks had ad libitum access to their feed while NS and CS bucks were under restricted feed (30% intake of C bucks) to induce nutritional stress. The HS and CS bucks were exposed to solar radiation for six hours a day between 10:00 h to 16:00 h to induce heat stress. The data was analyzed using repeated measures analysis of variance. There were significantly (P<0.01) higher standing time in ad libitum (C and HS) fed groups as compared to restricted fed (NS and CS) groups. However, the highest (P<0.01) lying time was recorded in CS group. The highest (P<0.01) drinking frequency was recorded in CS group while the lowest in NS group. The highest (P<0.01) defecating frequency was recorded in C group while the lowest in CS group. The highest (P<0.01) water intake was recorded in both HS and CS groups. The animals exhibited different physiological adaptive behaviour in morning and afternoon. The respiration rate (RR), pulse rate (PR) and rectal temperature (RT) were higher (P<0.01) in ad libitum fed groups in morning while in the afternoon it was higher (P<0.01) in both HS and CS groups. Both skin temperature of head and scrotum in afternoon differed significantly (P<0.01) between the groups. The highest plasma total protein (P<0.01) and total cholesterol (P<0.05) was established in NS groups as compared to other groups. Plasma triglycerides, plasma urea and plasma urea nitrogen also differed significantly (P<0.01) between the groups. Further, the higher plasma cortisol (P<0.01) and aldosterone (P<0.05) was recorded in CS group as compared to othergroups. The higher expression of adrenal Heat Shock Protein 70 (HSP70) messenger Ribonucleic acid (mRNA) was reported in CS goats. However, the higher expression of hepatic HSP70 mRNA was reported in HS goats. The highest degree of degenerative changes and hyperactivity of endocrine cells was recorded in CS group liver and adrenal gland respectively. It can be concluded from this study that when two stressors occur simultaneously, they may have severe impact on adaptive capabilities of Osmanabadi bucks as compared to that would occur individually. This is evident from the significantly higher behavioural, physiological responses and endocrine responses in CS group. Further, the study indicated that Osmanabadi bucks possess the capability to adapt to the detrimental effects of environmental stresses which is evident from the significant interaction of treatment and experimental days on majority of the parameters studied.